Effect of neem leaf and banana pulp extracts on shelf life and quality of mango (Mangifera indica L.): Effect of plant extract on shelf life of mango (Journal of the Bangladesh Agricultural University, 2018)
The study was carried out to minimize the postharvest loses and extend shelf life of mango fruitby maintaining physico-chemical properties. The variety selected for the study was “Amrapali”. Freshly harvested mango was treated with different concentrations (20% and 40%) of neem leaf and banana pulp extract alone or in combination. Untreated mango was considered as control. All treated and untreated mango was kept into paper cartons at room condition. The treated fruits showed significant differences in case of total soluble solids content, titratable acidity, vitamin C, disease incidence, disease severity and shelf life in comparison to control fruits. Among the treatments, T2 (neem leaf extract at 20%) and T5 (neem leaf extract 40% + banana pulp extract 40%) treatments showed longer shelf life (9.92 and 10.25 days, respectively), slower changes in color (score 2.77 and 2.93, respectively) and firmness (score 2.67 and 2.77, respectively); less disease severity (score 2.93 and 3.57, respectively), disease incidence (46.67% and 60.00%) and lower loss in weight (38.04% and 35.17%, respectively) at 9 DAT (Days after treatment). On the other hand, total soluble solid was highest in T3 (neem leaf extract 40%) treated fruitswith18.73% more Brix at 13 DAT in comparison to control and other treatments. The effectiveness of the treatment T5 (neem leaf extract 40% + banana pulp extract 40%) was meaningful which could be recommended for maintenance of postharvest quality of mango stored in ambient conditions.J. Bangladesh Agril. Univ. 16(3): 343–350, December 2018